Mangan Linjo “Kademangan Lingkungan Ijo” Upaya Menekan Angka Stunting dengan Budaya Konsumsi Sayur Organik di RW 04 RT 02 Kelurahan Kademangan Kota Probolinggo - Veronica Sri Astuti N. (Abdi Panca Marga, 2019)
Communities in Kademangan Village precisely in RW 04 RT 02, are still among those who are less concerned about healthy eating patterns. They still ignore the importance of the intake of nutrients needed by the body. Poor nutrition can lead to various health problems, one of which is stunting Stunting is a condition of growth failure in children (body and brain growth) due to malnutrition for a long time. Thus, children are shorter than normal children their age and have a delay in thinking. Malnutrition in a long time that occurs from the fetus in the womb until the beginning of the child's life (First 1000 Days of Birth). For this reason, community service activities by Panca Marga University Probolinggo 2019 KKN students are realized by realizing the "Mangan Linjo" program, which is an abbreviation of the Ijo Kademangan Lingkungan. The "Mangan Linjo" program aims to help the community in Kademangan Village to build a green environment containing 180 organic polybags. The method used is to directly involve the local community during the activity, so that in addition to getting an appeal, this program physically facilitates the community to get organic vegetables easily and cheaply. With this program, the community is aware of the importance of good nutrition through the use of organic vegetables and makes this program a sustainable program after feeling the benefits Keywords: Kademangan Village, Diet, organic vegetable plants